THE RELATIONSHIP BETWEEN KNOWLEDGE AND SELF-CARE IN ELDERLY PATIENTS WITH HYPERTENSION - Widiasti, Oktawiani Catur; Prakoso, Adi Buyu; Firdaus, Insanul (LPPM Universitas Duta Bangsa Surakarta, 2025)
Hypertension is one of the degenerative diseases commonly experienced by the elderly and is known as the